Utopia or Dystopia: The Dichotomy of “The Social Dilemma” Documentary in Shaping Public Perception - Fikriyah, Binta Ulfatul; Rahmanto, Andre Noevi; Wijaya, Mahendra; Hastuti, Dita Angelia Dwi (Universitas Muhammadiyah Yogyakarta, 2024)
Today's technology industry faces numerous issues, including scandals, data theft, consumer complaints, technology addiction, fake news, political polarization, and hacking. These problems are raised in the Netflix docudrama The Social Dilemma. This research discusses how algorithms and social media platform design can manipulate user behavior in both utopian and dystopian ways. It analyzes these dynamics through economic, political, sociocultural, and media perspectives, using Christian Fuchs' critical theory approach with critical discourse analysis and semiotics. The findings show that algorithms act as a double-edged sword. In a dystopian context, technology creates a bleak future in which it controls and damages human life. Conversely, in a utopian context, industrial technology has the potential to foster a more positive public perception. This research successfully explores how the increasing reliance on technology for work affects individuals' understanding of truth and shapes their perspectives on various aspects of life. By combining critical discourse analysis and semiotics, this study comprehensively analyzes the implications of digital labor on both utopian and dystopian narratives.